Pengembangan Kecerdasan Emosional Melalui Pembelajaran Sastra Anak Di Kelas Rendah - Jihan Ulfa Talita (Prodi PGSD Unsultra, 2024)
Emotional intelligence is an essential component in children's development that affects their academic and social success. This study aims to analyze the role of children's literature learning in developing students' emotional intelligence in lower elementary school grades. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and document analysis. The results of the study indicate that the integration of children's literature in learning is effective in increasing empathy, emotional management, and students' social skills. Therefore, it is recommended that teachers utilize children's literature as a medium to develop students' emotional intelligence.